PERNIKAHAN BERWALIKAN HAKIM Analisis Fikih Munakahat dan Kompilasi Hukum Islam - A., Aspandi (Ahkam: Jurnal Hukum Islam, 2017)
This article aims to descriptively analyze the case when a woman is going to get married under guardian of the Judge from the perspective of Islamic jurisprudence. The finding confirms that a womanâs marriage under the guardian of the Judge whether or not her biological guardian is still alive is considered legal from the perspective of either Islamic sharia or the Compilation of Indonesian Islamic Jurisprudence. In this case the Judge functions as the replacement of the womanâs biological guardian for some conditions accepted by the sharia such as emergency situation.Keywords: Pernikahan, Wali Hakim, KHI